Direct regulation of pluripotency genes by Nr5a2. - Shue, Bing Hong. (2012)
Nuclear receptor subfamily 5 group A member 2 (Nr5a2), also known as Liver Receptor Homolog -1 or LRH-1, is an orphan nuclear receptor found to be involved in important metabolic processes such as bile acid metabolism, steroidogenesis and liver development. Interestingly, Nr5a2 has recently been shown to be able to replace Oct4 in the factor mediated reprogramming of terminally differentiated cells back to a pluripotent state. Furthermore, in a genome-wide screen, ectopic expression of Nr5a2 was found to greatly enhance the conversion of epiblast stem cells to ground state pluripotency. However, the mechanism in which Nr5a2 perform such feats remain unclear. In order to dissect the role of Nr5a2 in reprogramming, we conducted experiments to investigate its direct regulation of pluripotency genes in mouse embryonic stem cells (mESCs). Ectopic expression of Nr5a2 in mESC resulted in the upregulation of pluripotency genes Nanog, Klf2 and Tbx3. Chromatin immunoprecipitation assays show that Nr5a2 binds to the promoters of Nanog, Tbx3 and Klf2. The direct binding of Nr5a2 was further validated with electrophoretic mobility shift assays. Using reporter assay, it was also shown that Nr5a2 regulates the Nanog enhancer activity. In summary, this study identified potential pluripotent targets of Nr5a2 in mESC.